Dysentry from gastroenteritis in infancy - Pitono Soeparto; Liek Djupri; Haroen Noerasid; Darto Saharso (Indonesian Pediatric Society, 1981)
Sixty three infants aged below 3 years suffering from dysentery form gastroenteritis were investigated. The investigation included clinical symptoms, course of the disease, stool ova and parasites and stool cultures for enterobacterial pathogens.Stool examinaJions revealed: 25.4% Entamoeba histolytica, 22.2% E.E. coli, 15.9% Salmonellae, 1.6% E.E. coli and Salmonella, 1.6% E.E. coli and E. histolytica and 1.6% Staph. aureus.The etiologic agent in the remaining 31.8% oj the patients remained unknown.The clinical features, the possible pathogenesis and treatment of the discovered pathogens are briefly discussed.